Maternal Perinatal Telemonitoring in the Context of the Coronavirus Disease 2019 Pandemic in a Tertiary Health Center in Peru - Novoa, Rommy H.; Meza-Santibañez, Luis; Melgarejo, Wilder E.; Huang-Yang, Xin; Guevara-Ríos, Enrique; Torres-Osorio, Juan; Aponte-Laban, Rosa; Jáuregui-Canchari, Vladimir; Rodríguez-Hilario, Noe; Ventura, Walter (American Journal of Perinatology, 2022)
Objective This study aimed to describe the characteristics of a telemonitoring program that was rapidly implemented in our institution as a response to the coronavirus disease 2019 (COVID-19) pandemic, as well as the maternal and perinatal outcomes of women who attended this program.Study Design Retrospective study of patients via phone-call telemonitoring during the peak period of the COVID-19 pandemic (May 2020–August 2020). Maternal and perinatal outcomes were collected and described. Health providers' satisfaction with the telemonitoring program was assessed via an email survey.Results Twenty-three (69.7%) health providers answered the survey. The mean age was 64.5 years, 91.3% were OB/GYN (obstetrician-gynecologist) doctors, and 95% agreed that telemonitoring is an adequate method to provide health care when in-person visits are difficult. The 78.7% of scheduled telemonitoring consultations were finally completed. We performed 2,181 telemonitoring consultations for 616 pregnant women and 544 telemonitoring consultations for puerperal women. Other medical specialties offering telemonitoring included gynecology, reproductive health, family planning, cardiology, endocrinology, and following up with patients with reactive serology to severe respiratory syndrome coronavirus 2 (SARS-CoV-2). The majority of the population attending our telemonitoring program were categorized as the lowest strata, i.e., III and IV, according to the Human Development Index, and approximately 42% were deemed as high-risk pregnant women. Additionally, we reported the perinatal outcomes of 424 (63%) pregnant women, the most relevant finding being that approximately 53% of them had cesarean sections.Conclusion Telemonitoring is an adequate method of continuing the provision of prenatal care when in-person visits are difficult in situations such as the COVID-19 pandemic. Telemonitoring is feasible even in institutions with no or little experience in telemedicine. The perinatal outcomes in women with telemonitoring seem to be similar to that in the general population.Key Points
Keywords: telemonitoring; telemedicine; prenatal care; COVID-19; pandemic; perinatal outcomes